EFEKTIVITAS MODEL PEMBELAJARAN STAD BERBASIS FLIPPED CLASSROOM TERHADAP AKTIVITAS BELAJAR DAN PEMAHAMAN KONSEP LAPORAN KEUANGAN DI SMK - Marbun, Theresia; Hendripides; Syabrus, Hardisem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the STAD (Student Teams Achievement Division) learning model based on Flipped Classroom in improving student learning activities and conceptual understanding of financial statements at SMK Perbankan Riau. The research employed a quantitative approach with a quasiexperimental one-group pretest-posttest design, involving 24 students of class XII Akuntansi 2 as the total sampling. Data were collected through concept comprehension tests, learning activity observation sheets, and questionnaires, and analyzed using descriptive analysis, the N-Gain formula, Shapiro-Wilk normality test, and paired sample t-test. The results showed that student learning activity increased consistently from 61% (Moderate) in the first meeting to 90% (Very Active) in the third, with an overall questionnaire average of 79% (Active). Conceptual understanding improved significantly, with the mean score rising from 40.21 (pretest) to 85.00 (posttest), all 24 students (100%) achieving the minimum competency standard (KKM), and an N-Gain percentage of 76.32% classified as Effective. The paired sample t-test yielded a significance value of 0.000 < 0.05, confirming that the STAD-Flipped model effectively enhances financial statement concept comprehension.